Pengaruh Belanja Modal Terhadap Infrastruktur Dan Pengembangan Ekonomi Antar Wilayah Provinsi Papua - Kristianus Hiktaop; Paulus Peka Hayon (Musamus University, 2019)
The objective of this study is to explain the consequences of capital expenditure on the infsrastructure and economic development between regions in the Papua province. A WarpPLS-based structural equation modeling analysis is chosen as the test model. Regional financial management is suspected to be less optimal because of the low self-reliance rate and the level of employee spending allocation is higher than the allocation rate of capital expenditure. The results of this study indicate that the financial management of the expenditure, especially capital expenditure, is positively affecting the infrastructure between the provinces of Papua. However, capital expenditure is negatively influential and does not imply the development of the regional economy. Infrastructure provides a negative impact on the economic development between regions during the research period. Thus, general financial management is not yet quality. Keywords: capital expenditure, infrastructure, and Economic development